Does Sharia Dormitory Business Unit support Islamic University Sustainability? Market, Financial, and Maqashid Sharia Analysis - Mubarak, Zaki; Faridah, Rohana; Yuliani, Rahma; Sukarni, Sukarni; Fong, Michelle (Universitas Islam Negeri Raden Intan Lampung, 2023)
Islamic universities in Indonesia face challenges in sustaining operations and improving service quality. One approach to addressing these challenges is to establish business units within the universities, which can generate additional revenue and improve service delivery. To this end, some new Islamic state universities establishing business units as part of their efforts to change institutional status to a Public Service Agency (BLU). This study assess whether a sharia dormitory business unit can support the sustainability of an Islamic state university by analyzing market potential, financial feasibility, and compliance with maqashid sharia. The study draws on a survey of 200 respondents to assess the market demand for the business unit and conducts a feasibility analysis based on Net Present Value (NPV), Pay Back Period (PP), and maqashid sharia aspects. The paper argues that the sharia dormitory business units can contribute to Islamic state universities sustainability by generating additional revenue, enhancing the quality of service to students, and aligning with maqashid sharia principles.